Finding methods of diagnosis and treatment of dental diseases in patients with gastroesophageal reflux disease - Bida, Віталій Іванович; Doroshenko, Микола Максимович (Actual Dentistry, 2023)
Introduction. Damage to the oral cavity is characteristic of a number of diseases of the gastrointestinal tract, and especially for such an acid-dependent disease as gastroesophageal reflux disease (GERD). Goal. Assessment of the dental status of patients with GERD and pathology of the hard tissues of the teeth, requiring the manufacture of dental orthopedic structures, depending on the treatment of the underlying PPI disease. Research methods. Survey, primary examination, evaluation of oral hygiene, condition of hard dental tissues and periodontal tissues using Green-Vermillion indices, caries intensity index (CVI), pH-metry of mixed saliva using SanXin SX 610 portable pH-meter potentiometer, manufactured by SanXin Instrumentation (China), the study of taste sensitivity according to Bernstein, the presence of plaque on the t ngue according to the method of E.G. Winkel et al. (2003) with the deduction of the WTC (Winkel Tongue Coating) index. Halitosis was diagnosed according to the method of R. Seemann (2002). The results. When assessing the dental status of patients with GERD, both those who took PPIs and those who did not take PPIs, when orthopedic treatment was needed, high values of KPV, OHI-S, PI, WTCI indices, unsatisfactory state of oral hygiene were found , a shift in the acid-alkaline balance and a change in taste sensitivity. It was found that the dental status of patients with GERD who did not take proton pump inhibitors was worse compared to patients who used them symptomatically as prescribed by a doctor. Conclusions. The dental status of patients with GERD depends on whether or not to take PPIs, the age of the patient, the duration and severity of the underlying disease.